Practice Guidelines in Neurorehabilitation - Platz, Thomas (Neurology International Open, 2017)
Practice guidelines are scientifically based practice recommendations. They can be consensus-based and provided by a single medical society (S1 guideline) or developed by a group of national medical societies with a structured consensus process (S2k guideline). S2k guidelines are a good opportunity to develop valid practice guidelines with a broad supporting base when health topics are either complex or when clinical evidence is limited. Evidence-based guidelines rest on a systematic search and critical appraisal of the available evidence and represent the highest quality level for guidelines; they can be developed by single medical societies (S2e guideline) or jointly by several national medical societies (S3 guideline). They reflect the state of the art and generate a high degree of confidence that their recommendations support optimal treatment. The German neurorehabilitation society (DGNR) provides evidence-based guidelines for motor rehabilitation after stroke (arm, mobility, spasticity).
Keywords: guideline; stroke; neurorehabilitation; evidence